EVALUATION OF THE WORK FLOW OF GOVERNMENT PUBLIC RELATIONS MONITORING MEDIA IN THE MANAGEMENT OF ENVIRONMENTAL ISSUES AT THE REGIONAL LEVEL - Carolline Sekar Karunia Putri; Diah Fatma Sjoraida; Agus Rahmat (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to evaluate the alignment of the media monitoring workflow at the Protocol and Leadership Communication Section (Prokopim) of the Bandung City Regional Secretariat with national standards in managing the issue of waste accumulation. The research method employed is descriptive qualitative with a post-positivism approach, utilizing data collection techniques such as participatory observation and structured interviews with the issue analysis team. The findings indicate that Prokopim has successfully implemented media monitoring as a strategic communication management and early warning instrument to mitigate leadership reputation crises. However, an in-depth analysis reveals significant methodological gaps compared to the Media Monitoring Guidelines for Government Public Relations Activities. These gaps include the absence of standardized operational parameters—such as defined keywords, units of analysis, and coding protocols—leaving data screening heavily reliant on manual processes and personnel subjectivity. Furthermore, cross-sectoral coordination under the